Estratégias metodológicas para o estudo das funções trigonométricas e funções hiperbólicas - Santos, Diego Rabelo dos (Universidade Federal Rural do Semi-Árido, 2021)
Teaching mathematics in a way to contextualize and apply the concepts to those who have this discipline as a target has become increasingly challenging in the midst of a society with a vast technological prowess. Several researchers are dedicated to seeking alternative methods to present these contents to their apprentices. Aiming at this end, this work presents methodological approaches in carrying out the study of trigonometric functions and hyperbolic functions. These types of functions have many applications in various fields of science. Topics like these are a priori addressed in high school courses, and higher education courses, which have mathematics as a basis. Here, a theoretical study of these two types of functions is made based on alternative methodological tools for their learning. Among these tools, we can mention software, mobile and tablet applications and programming languages. The ideas presented in this work can help those interested in the subject to seek a more effective learning, through technological resources widely used by the segments of scientific research and social media
Keywords: Funções Trigonométricas; Funções Hiperbólicas; Ensino; Tecnologia; Trigonometry; Hyperbolic Functions; Teaching; Technology; CIENCIAS EXATAS E DA TERRA::MATEMATICA